Cathode and electrochemical cell using same

The cathode for electrochemical cells, featuring an inorganic filler with a specific aspect ratio, addresses the mechanical strength issues in SOECs, enhancing durability and preventing deformation.

JP7662379B2Active Publication Date: 2025-04-15NORITAKE MACHINE TECHNO CO LTD

Patent Information

Application Number
JP2021061909
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-31
Publication Date
2025-04-15
Estimated Expiration
2041-03-31

AI Technical Summary

Technical Problem

Solid oxide electrolyser cells (SOEC) experience deformation and damage due to uneven gas partial pressures during long-term operation, necessitating the development of hydrogen electrodes with enhanced mechanical strength.

Method used

A cathode for electrochemical cells is designed with a matrix of inorganic material and an inorganic filler, where the average aspect ratio of the filler is between 0.01 and 0.5, providing improved mechanical strength.

Benefits of technology

The cathode with inorganic fillers achieves superior mechanical strength, reducing deformation and damage during SOEC operation, and can be applied to various electrochemical cells, including those used in oxygen sensors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007662379000003
    Figure 0007662379000003
  • Figure 0007662379000004
    Figure 0007662379000004
  • Figure 0007662379000005
    Figure 0007662379000005
Patent Text Reader

Abstract

To provide a cathode having high mechanical strength.SOLUTION: A cathode is for use in an electrochemical cell. The cathode contains a matrix that is composed of an inorganic material, serving as a cathode, and inorganic fillers contained in the matrix. The inorganic fillers have an average aspect ratio (minor axis / major axis ratio) of 0.01-0.5.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a cathode and an electrochemical cell using the same. [Background technology]

[0002] For example, solid oxide electrolyser cells (hereinafter sometimes simply referred to as "SOECs") are being developed as electrolysis devices capable of efficiently producing hydrogen by utilizing the electrolysis reaction of water. SOECs are typically based on a dense, laminar solid electrolyte layer made of an oxide ion conductor, with a porous air electrode (anode) formed on one side of this solid electrolyte layer, and a porous hydrogen electrode (cathode) formed on the other side (see Patent Document 1 below). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2011-210420 A Summary of the Invention [Problem to be solved by the invention]

[0004] During operation of the SOEC, the electrolysis reaction of water continues to proceed at high temperatures, so the water (H 2 O) and hydrogen (H 2 ) tends to be non-uniform in gas partial pressure. It is known that this can cause deformation or damage to the hydrogen electrode when the SOEC is operated for a long period of time. In other words, there is a demand for the development of a hydrogen electrode with excellent mechanical strength. Although the above description has been given using an SOEC as an example, there is also a demand for the development of such a cathode for electrochemical cells used in, for example, oxygen sensors. The present invention has been made in view of the above circumstances, and its main object is to provide a cathode with excellent mechanical strength. [Means for solving the problem]

[0005] In order to achieve this object, the present invention provides a cathode for use in an electrochemical cell. The cathode includes a matrix made of an inorganic material that functions as a cathode, and an inorganic filler contained in the matrix, and the inorganic filler has an average aspect ratio (minor axis / major axis ratio) of 0.01 to 0.5. A cathode containing such an inorganic filler can achieve excellent mechanical strength.

[0006] In a preferred embodiment of the cathode disclosed herein, the inorganic filler has an average minor axis of 0.05 μm or more and an average major axis of 10 μm or less, and the cathode containing such an inorganic filler can achieve superior mechanical strength.

[0007] In a preferred embodiment of the cathode disclosed herein, the inorganic filler is mainly composed of a single crystal structure, which makes it possible to obtain a cathode having superior mechanical strength.

[0008] In a preferred embodiment of the cathode disclosed herein, the inorganic filler contains alumina. Alumina is highly versatile and can therefore be suitably used in the technology disclosed herein.

[0009] In a preferred embodiment of the cathode disclosed herein, the inorganic material contains nickel oxide. According to the study by the present inventors, it was found that an inorganic filler containing alumina or the like and an inorganic material containing nickel oxide or the like are likely to react with each other during firing to form an insulating layer. This is undesirable because it may cause deformation of the hydrogen electrode and make it impossible to obtain a suitable electrochemical cell. On the other hand, it was found that when alumina with a properly adjusted shape (specifically, average aspect ratio, etc.) is used, the reaction with nickel oxide is suitably suppressed, and therefore a suitable electrochemical cell can be obtained. In other words, inorganic materials containing nickel oxide are suitable as targets for applying the technology disclosed herein.

[0010] In a preferred embodiment of the cathode disclosed herein, the cathode is plate-shaped, and in an SEM image of a cross section in the thickness direction of the cathode, 90% or more of the inorganic fillers have an acute angle θ of 10° or less between the major axis of the inorganic filler and either the thickness direction or the direction perpendicular to the cross section (hereinafter, this embodiment may be simply referred to as "having orientation"). In this way, by providing orientation to the inorganic filler in the cathode, a cathode with more suitably improved mechanical strength can be obtained.

[0011] In another aspect, the present invention provides an electrochemical cell including any of the cathodes disclosed herein, an anode, and a solid electrolyte layer disposed between the cathode and the anode, and also provides a water production device including such an electrochemical cell, and a hydrogen production method for producing hydrogen using the hydrogen production device. [Brief description of the drawings]

[0012] [Figure 1] FIG. 1 is a diagram illustrating a structure of an SOEC according to an embodiment. [Figure 2A] FIG. 2 is a diagram showing an embodiment of an inorganic filler oriented in a direction perpendicular to a cross section in a thickness direction of a hydrogen electrode (cathode). [Figure 2B] FIG. 2 is a diagram showing an inorganic filler according to an embodiment oriented in the thickness direction of a hydrogen electrode (cathode). [Diagram 3] FIG. 1 is a schematic diagram for explaining a hydrogen production device according to an embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] Hereinafter, preferred embodiments of the present invention will be described. Matters other than those specifically mentioned in this specification and that are necessary for the implementation of the present invention can be understood as design matters of those skilled in the art based on the prior art in the relevant field. The present invention can be implemented based on the content disclosed in this specification and common general knowledge in the art. Note that the following embodiments are not intended to limit the technology disclosed herein to such embodiments. Also, in the drawings shown in this specification, members and parts having the same function are denoted by the same reference numerals for explanation. And the dimensional relationships (length, width, thickness, etc.) in each figure do not reflect the actual dimensional relationships. In this specification and the claims, when a predetermined numerical range is denoted as A to B (A and B are arbitrary numerical values), it means A or more and B or less. Therefore, it includes cases where it exceeds A and is less than B.

[0014] Also, in this specification and the claims, the "anode" is an electrode from which electrons flow out to an external circuit, and the "cathode" means an electrode into which electrons flow from an external circuit. Further, in this specification and the claims, the "plate-like" can refer to a mode having two wide surfaces and having a thickness between the wide surfaces. Such wide surfaces can have various shapes such as rectangular, circular, and elliptical. Also, although not particularly limited, when the major axis of the wide surface is s, the minor axis is t, and the thickness is u, generally u < t < s can be set. Also, such u can be u ≤ (1 / 2)t, u ≤ (1 / 3)t, u ≤ (1 / 5)t, etc.

[0015] <soec1> 1 is a cross-sectional view showing a schematic diagram of an SOEC 1 according to an embodiment. As shown in the figure, the SOEC 1 according to this embodiment generally includes a hydrogen electrode (cathode) 10, a solid electrolyte layer 12, and an air electrode (anode) 14. Each component will be described in detail below.

[0016] (Hydrogen pole 10) The hydrogen electrode (cathode) 10 has a role of supplying oxide ions at a relatively high concentration to one surface of the solid electrolyte layer 12. The hydrogen electrode 10 generates oxide ions from, for example, high-temperature steam and conducts the oxide ions toward the solid electrolyte layer 12. Therefore, the hydrogen electrode 10 is supplied with a gas (typically high-temperature steam or the like) that is a raw material for the oxide ions. The hydrogen electrode 10 includes a matrix (not shown) made of an inorganic material that functions as a hydrogen electrode, and an inorganic filler 20 contained in the matrix. As such an inorganic material, any material that is used for a hydrogen electrode of a conventionally known SOEC can be used without any particular limitation. For example, a material that includes particles of a metal (catalyst) and a metal oxide (oxide having oxide ion conductivity) can be used. As such a metal, one or more selected from the group consisting of nickel (Ni), cobalt (Co), iron (Fe) and copper (Cu), or an alloy containing them can be used. As such a metal oxide, for example, stabilized zirconia (SZ) and doped ceria (DC) can be used. And stabilized zirconia is Y 2 O 3 ,Sc 2 O 3 ,Yb 2 O 3 ,Gd 2 O 3 ,CaO,MgO,CeO 2 Zirconia (zirconium dioxide: ZrO 2 The doped ceria can be Sm 2 O 3 , Gd 2 O 3 and Y 2 O 3 Ceria (cerium oxide: CeO 2 ). The average particle size of the inorganic material is not particularly limited as long as the effect of the technology disclosed herein is exhibited, but may be about 0.1 to 10 μm (for example, about 0.5 to 5.0 μm). In this specification, the term "average particle size" refers to the particle size D50 value (also called the median size) corresponding to the cumulative 50% from the fine particle side with a small particle size in the volume-based particle size distribution measured based on the laser diffraction / light scattering method.

[0017] The inorganic filler 20 is not particularly limited as long as the effect of the technology disclosed herein is exhibited. For example, alumina, silica, titanium oxide, yttrium oxide, zirconia, zirconia stabilized by yttrium or other rare earth elements, magnesia, barium sulfate, aluminum hydroxide, etc. can be mentioned. Among them, alumina, etc., which has high versatility, can be preferably used. These can be used alone or in combination of two or more. The content ratio of the stabilizer is not particularly limited, but it is preferably about 5 to 10 mol% when the whole inorganic filler is taken as 100 mol%. Here, according to the study by the present inventors, it was found that when nickel oxide, etc. as the inorganic material and alumina, etc. as the inorganic filler are used together, they react during firing to form an insulating layer. This is not preferable because there is a risk that the hydrogen electrode will be deformed and an appropriate electrochemical cell cannot be obtained. On the other hand, it was found that when alumina with a shape (specifically, average aspect ratio, etc.) appropriately adjusted is used, the reaction with nickel oxide is suitably suppressed, and an appropriate electrochemical cell can be obtained. In other words, it can be said that inorganic materials containing nickel oxide are suitable targets for application of the technology disclosed herein.

[0018] The inorganic filler 20 has an average minor axis / major axis ratio (i.e., average aspect ratio) of 0.01 to 0.5. Although not particularly limited, from the viewpoint of more suitably improving the mechanical strength of the hydrogen electrode 10, the average aspect ratio can be preferably set to 0.02 or more (e.g., 0.05 or more). Moreover, the average aspect ratio can be preferably set to 0.4 or less, 0.3 or less, 0.2 or less, or 0.1 or less.

[0019] In the present specification and claims, the term "average aspect ratio" refers to the average value of the minor axis / major axis ratio of a plurality of particles. That is, the average aspect ratio is a value indicating the average particle shape of the particles. From the above average aspect ratio, the inorganic filler particles may have various shapes, such as flat, scaly, flake-like, rod-like, elliptical, fibrous, and needle-like shapes. Among them, from the viewpoint of easily providing the orientation described later, flat, scaly, flake-like, and the like shapes are preferred.

[0020] The average aspect ratio can be determined, for example, by electron microscope observation. As a specific procedure, for example, a scanning electron microscope (SEM) is used to observe a predetermined number of particles (for example, 50 or more) contained in the inorganic filler to be measured, and a rectangle with the smallest circumscribing area is drawn for each particle image. Then, for the rectangle drawn for each particle image, the length of the short side (minor axis value) is divided by the length of the long side (major axis value) to calculate the minor axis / major axis ratio (aspect ratio) of each particle. Then, the average aspect ratio can be determined by arithmetically averaging the aspect ratios of the predetermined number of particles. The aspect ratio and average aspect ratio of each particle can be determined using general image analysis software. When the inorganic filler particles are, for example, flat, scaly, flake-like, rod-like, elliptical, etc., the minor axis and major axis of the broad surface are calculated.

[0021] The average minor axis of the inorganic filler 20 (i.e., average minor axis) is not particularly limited as long as the effects of the technology disclosed herein are exerted, but is generally 0.01 μm or more, for example 0.05 μm or more, and from the viewpoint of facilitating orientation, it can be preferably 0.1 μm or more, more preferably 0.5 μm or more, 1 μm or more. The upper limit of the average minor axis is not particularly limited as long as the effects of the technology disclosed herein are exerted, but can be generally 2.5 μm or less, for example 2 μm or less, 1.5 μm or less.

[0022] In the present specification and claims, the term "average minor axis" refers to the average minor axis of a plurality of particles (e.g., 50 or more). The minor axis of each particle can be calculated as the arithmetic average of the lengths of the short sides of the rectangle that circumscribes each particle image obtained by SEM and has the smallest area, similar to the aspect ratio described above.

[0023] The average major axis of the inorganic filler 20 (i.e., average major axis) is not particularly limited as long as the effects of the technology disclosed herein are exhibited, but is generally 1 μm or more, and from the viewpoint of facilitating orientation, can be preferably 2 μm or more, 5 μm or more. The upper limit of the average major axis is not particularly limited as long as the effects of the technology disclosed herein are exhibited, but can be generally 20 μm or less, for example 10 μm or less.

[0024] In the present specification and claims, the term "average major axis" refers to the average value of the major axes of a plurality of particles (e.g., 50 or more). The major axis of each particle can be calculated as the arithmetic average value of the lengths of the long sides of the rectangles that circumscribe each particle image obtained by SEM and have the smallest area, similar to the aspect ratio described above.

[0025] Further, the average thickness (i.e., the mean thickness) of the inorganic filler 20 is not particularly limited as long as the effects of the technology disclosed herein can be achieved, but it can generally be 0.01 μm or more, for example, 0.03 μm or more. And the upper limit of the above mean thickness is not particularly limited as long as the effects of the technology disclosed herein can be achieved, but it can generally be 0.1 μm or less, for example, 0.05 μm or less.

[0026] In addition, the "mean thickness" in this specification refers to the average value of the thicknesses of a plurality (for example, 50 or more) of particles. The average thickness of each particle can be determined by electron microscope (SEM) observation. As a specific procedure, for example, a sample in which the particles to be measured are solidified with resin is prepared, and the cross-section of the sample is observed with a scanning electron microscope. Then, the thickness (the length across the thickest part) of a predetermined number (for example, 50 or more) of particles included in the cross-section is measured, and the mean thickness can be obtained by arithmetically averaging the thicknesses of the predetermined number of particles. Note that the thickness of the inorganic filler can be referred to as the length between the wide surfaces. Also, although not particularly limited, when the major axis of the inorganic filler is s, the minor axis is t, and the thickness is u, generally u < t < s can be obtained. And although not particularly limited, u ≦ 1 / 2t, u ≦ 1 / 3t, u ≦ 1 / 5t, etc. can be set.

[0027] In a preferred embodiment, the hydrogen electrode 10 is plate-shaped, and 90% by number or more of the inorganic fillers 20 observed in an SEM image of a cross section (i.e., XY cross section) in the thickness direction (i.e., Y direction) of the hydrogen electrode have an acute angle θ of 10° or less, which is the acute angle between the major axis of the inorganic filler and the thickness direction or the direction perpendicular to the cross section. In an embodiment in which the value of θ is 10° or less, the mechanical strength of the hydrogen electrode 10 is more preferably improved. The SEM image is taken at random, and one or more images are taken. The magnification of the SEM image is not particularly limited, but may be, for example, about 1000 to 5000 times. The value of θ may be 10° or less, preferably 9° or less, and more preferably 7° or less. The expression "90% by number or more" may mean that, when the number of inorganic fillers confirmed in the SEM image is n, the number is 0.9×n or more. 2A shows that the inorganic filler (e.g., inorganic filler 20a) is oriented in a direction perpendicular to the cross section in the thickness direction of the hydrogen electrode 10a, and FIG. 2B shows that the inorganic filler (e.g., inorganic filler 20b) is oriented in the thickness direction of the hydrogen electrode 10b. For example, if n=20, then 18 or more θ (θ a ,θ b ) should be 10° or less. The value of n cannot be generally defined because it depends on the cross section to be measured, but from the viewpoint of ensuring accuracy, it is preferably 20 or more, more preferably 30 or more, and even more preferably 50 or more (e.g., 100 or more). In addition, for example, when two or more SEM images are obtained, the number of inorganic fillers observed in each image is totaled, and the value of θ for 90% or more by number of them should be 10° or less.

[0028] The crystallinity of the inorganic filler 20 is not particularly limited as long as the effect of the technology disclosed herein is exhibited. That is, the inorganic filler 20 may be mainly composed of, for example, a single crystal structure, or may be mainly composed of a polycrystalline structure. From the viewpoint of obtaining a hydrogen electrode 10 with superior mechanical strength, it is preferable that the inorganic filler 20 is mainly composed of a single crystal structure. For example, a commercially available inorganic filler having such crystallinity can be purchased and used. Here, in the present specification and claims, "mainly composed of a single crystal (or polycrystalline) structure" can mean that 60 volume % or more, 70 volume % or more, typically 80 volume % or more (for example, it can be 90 volume % or 100 volume %) of the total inorganic filler particles is a single crystal structure (or a polycrystalline structure).

[0029] The hydrogen electrode 10 may contain other components as long as they do not significantly impair the effects of the technology disclosed herein. For example, when particulate components other than inorganic fillers are contained as such optional components, it is preferable that the particulate components also have an average aspect ratio similar to that of the inorganic filler. The other components can be selected from conventionally known components that can be contained in the hydrogen electrode of an SOEC without any particular restrictions, and detailed explanations are omitted since they do not limit the technology disclosed herein.

[0030] The thickness of the hydrogen electrode 10 (i.e., the length in the Y direction) is not particularly limited, but is preferably about 80 μm or less, typically 70 μm or less, for example 50 μm or less. From the viewpoint of increasing catalytic active sites and exerting the function of the layer at a high level, it is preferably about 10 μm or more, for example 20 μm or more. The hydrogen electrode 10 may have a porous structure. The porosity of the hydrogen electrode 10 is not particularly limited, but is preferably about 1 vol.% or more, for example 5 vol.% or more, from the viewpoint of ensuring a sufficient contact area with the gas and improving gas diffusibility. From the viewpoint of maintaining high levels of electrical conductivity and mechanical strength, it is usually lower than the porosity of the fuel electrode support 12, and is preferably about 30 vol.% or less, typically 20 vol.% or less, for example 15 vol.% or less.

[0031] In this embodiment, the hydrogen electrode 10 has a single-layer structure, but is not limited thereto. For example, the hydrogen electrode 10 may have a two-layer structure of a hydrogen electrode support and a hydrogen electrode active layer, or may have a structure of, for example, three or more layers. The material constituting the hydrogen electrode support may be the same as that of the hydrogen electrode support of a conventionally known SOEC, without any particular limitation.

[0032] (Solid electrolyte layer 12) As shown in FIG. 1, the solid electrolyte layer 12 serves to conduct oxide ions. As a material for forming the solid electrolyte layer 12, any material (typically, an oxide ion conductor) used in a solid electrolyte layer of a conventionally known SOEC can be used without any particular limitation. Suitable examples include oxides containing elements such as zirconium (Zr), cerium (Ce), magnesium (Mg), scandium (Sc), titanium (Ti), aluminum (Al), yttrium (Y), calcium (Ca), gadolinium (Gd), samarium (Sm), barium (Ba), lanthanum (La), strontium (Sr), gallium (Ga), bismuth (Bi), niobium (Nb), and tungsten (W). Among them, yttria (Y 2 O 3 Zirconia stabilized with stabilizers such as ZrO 2 ), such as YSZ (Yttria stabilized zirconia) and gadolinia (Gd 2 O 3 ) and other doping agents. 2 ), for example, GDC (Gadolinium doped Ceria), etc. are preferred. These may be used alone or in combination of two or more. The content of the stabilizer or dopant is not particularly limited, but is preferably about 5 to 10 mol % when the entire oxide ion conductor is taken as 100 mol %.

[0033] The thickness of the solid electrolyte layer 12 (i.e., the length in the Y direction) is not particularly limited, but can be approximately 30 μm or less, typically 20 μm or less, for example 15 μm or less. From the viewpoint of suppressing the occurrence of defects such as gas leakage and cracks, the thickness can be approximately 3 μm or more, for example 5 μm or more. The porosity of the solid electrolyte layer 12 is not particularly limited, but from the viewpoint of preventing gas leakage, it is usually 5 vol.% or less, for example 2 vol.% or less. On the other hand, in order to form an extremely dense solid electrolyte layer 12 (for example, a porosity of 0.1 vol.% or less), stacking at the atomic level is required, and special and complicated operations are required. Therefore, from the viewpoints of workability, productivity, and low cost, it is approximately 0.2 vol.% or more, for example 0.5 vol.% or more.

[0034] (Air pole 14) The air electrode (anode) 14 may be a porous body in order to efficiently generate oxygen from oxide ions. The material constituting the air electrode 14 may be any material used for the air electrodes of conventionally known SOECs, without any particular restrictions. One suitable example is (La,Sr)MnO 3 (For example, La 0.8 Sr 0.2 MnO 3 (hereinafter referred to as LSM) and other perovskite oxides containing La, Sr, and Mn. 3 (For example, La 0.6 Sr 0.4 Chief of Staff 3 (hereinafter referred to as LSC) and (La,Sr)(Co,Fe)O 3 (For example, La 0.6 Sr 0.4 Co 0.2 Fe 0.8 O 3 Examples of perovskite oxides include those containing La, Sr, and Co, such as LSCF (hereinafter referred to as LSCF). The substitution ratios of the A and B sites of these LSM, LSC, and LSCF can be determined in various ways, and an appropriate substitution ratio can be used depending on the desired ion conductivity, reduction expansion coefficient, etc. These can be used alone or in combination of two or more types.

[0035] Also, the thickness of the air electrode 14 (i.e., the length in the Y direction) is not particularly limited, but from the viewpoint of reducing resistance, it can generally be 5 μm or more, typically 5 - 50 μm, for example, 10 - 30 μm. The air electrode 14 has a porous structure for improving gas diffusibility and oxidation reactivity. The porosity of the air electrode 14 is not particularly limited, but it is preferably generally 10% by volume or more, typically 10 - 30% by volume, for example, 15 - 25% by volume.

[0036] [Other forms] In the above embodiment, an SOEC including one set of an electrochemical cell in which a hydrogen electrode (cathode), an air electrode (anode), and a solid electrolyte layer are disposed between the hydrogen electrode and the air electrode has been described. However, the present invention is not limited thereto, and a mode in which a plurality of such electrochemical cells are stacked can be adopted. Further, if necessary, a reaction suppression layer may be provided between the solid electrolyte layer and the air electrode. Note that, as the material constituting the reaction suppression layer, the same materials as those of the conventionally known reaction suppression layers of SOECs can be used without particular limitation. In the above description, the hydrogen electrode (cathode) used in the SOEC has been described. However, the present invention is not limited thereto. The cathode disclosed herein can also be used, for example, in an electrochemical cell of an oxygen sensor.

[0037] <Manufacturing method of SOEC1> Next, a manufacturing method of SOEC1 according to an embodiment will be described. The manufacturing method according to this embodiment includes a green sheet production step (step 1), a green sheet lamination step (step 2), and a firing step (step 3). In such a manufacturing method, a so-called co-firing is carried out in which green sheets of each layer of the hydrogen electrode, the solid electrolyte layer, and the air electrode are laminated and then fired simultaneously. Hereinafter, each step will be described.

[0038] Green sheet production step (step 1): In this process, green sheets for each layer (hydrogen electrode, solid electrolyte layer, air electrode) constituting the SOEC 1 are prepared. Note that the green sheets for the layers other than the hydrogen electrode (i.e., the solid electrolyte layer and air electrode) are not particularly limited as long as they can be used in the manufacture of this type of SOEC, and are not a feature of the present invention, so detailed explanations are omitted. The following description focuses on the method for manufacturing the green sheet for the hydrogen electrode.

[0039] In this step, first, a slurry (including ink and paste) composition for forming a hydrogen electrode is prepared, which contains the inorganic material as described above, an inorganic filler, and, if necessary, a binder and a dispersion medium. The amount of the inorganic material is not particularly limited as long as the effects of the technology disclosed herein are exhibited, but can be within the range of approximately 50 to 70 mass% when the entire composition for forming a hydrogen electrode is taken as 100 mass%. The amount of the inorganic filler is not particularly limited as long as the effects of the technology disclosed herein are exhibited, but can be within the range of approximately 1 to 20 mass% when the entire composition for forming a hydrogen electrode is taken as 100 mass%.

[0040] The dispersion medium is not particularly limited, and a conventionally known dispersion medium can be appropriately selected and used. Examples include alcohol-based dispersion media such as methanol, ethanol, m-propanol, i-propanol, and n-butanol, toluene, choline, xylene, terpineol (α-terpineol, etc.), carbitols, methyl ethyl ketone, water, and mixtures thereof. The amount of the dispersion medium is not particularly limited as long as the effects of the technology disclosed herein are exhibited, but can be within the range of approximately 20 to 50 mass% when the entire hydrogen electrode forming composition is taken as 100 mass%.

[0041] The binder is not particularly limited, but for example, a resin material having thermoplasticity and being burned off by a baking process (typically, heating and baking at 200°C or higher) can be suitably used. By adding such a binder, the moldability of the green sheet can be improved. Suitable examples include natural polymer compounds such as polyvinyl butyral (PVB), carrageenan, and xanthan gum, cellulose polymers such as ethyl cellulose and carboxymethyl cellulose, acrylic resins, epoxy resins, phenolic resins, amine resins, and alkyl resins. The amount of the binder is not particularly limited as long as the effect of the technology disclosed herein is exhibited, but can be within the range of approximately 1 to 20 mass% when the entire hydrogen electrode forming composition is taken as 100 mass%.

[0042] In addition, conventionally known additives may be added to the composition as long as they do not significantly impair the effects of the technology disclosed herein. Examples of such additives include dispersants, plasticizers, antifoaming agents, release agents, antioxidants, thickeners, pore-forming materials, etc. The amount of the additives is not particularly limited as long as the effects of the technology disclosed herein are exhibited, but can be within the range of approximately 1 to 10 mass % when the entire hydrogen electrode-forming composition is taken as 100 mass %.

[0043] The hydrogen electrode-forming composition can be prepared using various known stirring and mixing devices such as a ball mill, mixer, disperser, and kneader. For example, the inorganic material, inorganic filler, binder, dispersion medium, and additives are charged into any stirring and mixing device, and stirred and mixed for a predetermined time (for example, about 1 to 2 hours), to prepare a homogeneous composition. In addition, considering the blade coating method described later, the viscosity of the hydrogen electrode-forming composition is preferably about 5 to 100 Pa·s (25°C-20 rpm) (preferably about 10 to 50 Pa·s, etc.). Such a viscosity can be measured, for example, using a commercially available viscometer.

[0044] In this step, a green sheet for a hydrogen electrode is then produced using the hydrogen electrode-forming composition prepared as described above. Here, with conventionally known coating methods (e.g., blade coating, screen printing, roll compaction molding, dip coating, etc.), it has been difficult to give the inorganic filler the above-mentioned orientation (i.e., the inorganic filler tends to be randomly arranged). However, as a result of intensive studies by the present inventors, it has been found that it is possible to give the inorganic filler the above-mentioned orientation by a coating method with appropriately adjusted conditions. An example of such a coating method will be described below.

[0045] First, a method for producing a hydrogen electrode green sheet in which inorganic filler is oriented in a direction perpendicular to the thickness direction of the hydrogen electrode will be described. A suitable example of such a production method is a blade coating method in which a hydrogen electrode forming composition adjusted to an appropriate viscosity (such as the viscosity described above) is discharged at an appropriate pressure from a gap in a blade adjusted to an appropriate size. The size of the gap can be determined, for example, from the solids concentration of the hydrogen electrode forming composition, taking into account the amount of volumetric shrinkage. By such a method, a hydrogen electrode green sheet in which inorganic filler is oriented in a direction perpendicular to the thickness direction of the hydrogen electrode can be obtained.

[0046] Next, a method for producing a hydrogen electrode green sheet in which the inorganic filler is oriented in the thickness direction of the hydrogen electrode will be described. A plurality of hydrogen electrode green sheets obtained as described above are stacked in the thickness direction, and then the stacked surface is placed upright so that it faces downward. The sheet is then cut to a desired thickness to obtain a hydrogen electrode green sheet in which the inorganic filler is oriented in the thickness direction of the hydrogen electrode.

[0047] Green sheet lamination process (Step 2): In this process, green sheets for the above-mentioned layers are laminated. Specifically, in this process, green sheets for the hydrogen electrode, solid electrolyte layer, and air electrode are laminated in this order to produce a laminate, which is a precursor of the SOEC.

[0048] Firing process (Step 3): In this process, co-firing is performed to fire the fabricated laminate. As a result, the green sheets of each layer are fired simultaneously, and the SOEC1 having a hydrogen electrode, a solid electrolyte layer, and an air electrode is fabricated. The firing temperature in this process can be, for example, about 1100°C to 1500°C. Also, the firing time can be, for example, about 1 hour to 5 hours.

[0049] [Other forms] In addition, in the above embodiment, the manufacturing method of the SOEC using the green sheets of the hydrogen electrode, the solid electrolyte layer, and the air electrode has been described. However, for example, in addition to the above green sheets, the green sheets of the hydrogen electrode support and the reaction inhibition layer may be fired together. That is, the green sheets of the hydrogen electrode support, the hydrogen electrode, the solid electrolyte layer, the reaction inhibition layer, and the air electrode can be laminated and co-fired. The materials constituting the hydrogen electrode support and the reaction inhibition layer can be used without particular limitation as the materials used for the hydrogen electrode support and the reaction inhibition layer of a conventionally known SOEC. Also, in such a case, for example, the one obtained by laminating and firing the green sheets of the hydrogen electrode support, the hydrogen electrode, the solid electrolyte layer, and the reaction inhibition layer is used as a half cell of the SOEC, and the SOEC can also be fabricated by laminating the green sheet of the air electrode on the half cell and further firing it.

[0050] <Hydrogen production apparatus 100 equipped with SOEC1> The SOEC 1 prepared as described above can be used in a hydrogen production device. FIG. 3 shows a hydrogen production device 100 according to one embodiment. As shown in the figure, the hydrogen production device 100 is roughly equipped with a power source 30 and a main body 40. The main body 40 according to this embodiment is equipped with the SOEC 1 as an electrochemical cell, a hydrogen electrode side flow path 42, and an air electrode side flow path 44. Here, the power source 30 can be a DC power source with a positive terminal electrically connected to the hydrogen electrode 10 (cathode) and a negative terminal electrically connected to the air electrode 14 (anode). The hydrogen production device 100 can be constructed by a method for constructing a conventionally known hydrogen production device, and is not a feature of the technology disclosed herein, so a detailed description will be omitted.

[0051] [Other aspects] In the above embodiment, the hydrogen production device is described as having one SOEC, but the present invention is not limited to this, and may have, for example, a stack of SOECs. Also, separators may be provided as necessary.

[0052] <Method for producing hydrogen using hydrogen production device 100> Next, a method for producing hydrogen using the hydrogen production device 100 according to one embodiment will be described. The hydrogen production method according to this embodiment includes a step of electrolyzing a raw material gas (step 4) and a step of recovering hydrogen obtained by the electrolysis (step 5). First, in step 4, the power supply 30 is turned on to start up the hydrogen production device 100. This starts up a current flowing in the direction from the air electrode 14 to the hydrogen electrode 10. Next, a raw material gas (here, high-temperature steam) is injected from the inlet 41 in the hydrogen electrode-side flow path 42. Then, the high-temperature steam is electrolyzed in the air electrode 10 to produce hydrogen (H 2 ) and oxide ions (O 2- ) Next, in step 5, the hydrogen obtained in step 4 is recovered. This recovery can be performed at the recovery port 43 in FIG. 3. In this manner, high-purity hydrogen can be obtained efficiently. The oxide ions generated as described above pass through the solid electrolyte layer 12 and are oxidized in the air electrode 14 to form oxygen (O 2 ) and electrons (e ― The oxygen thus produced can be discharged to the outside from the outlet 45 in the air electrode side flow path 44.

[0053] Test examples relating to the present disclosure will be described below, but it is not intended that the present invention be limited to such test examples.

[0054] <First test example> In this test example, the durability of the hydrogen electrode and the degree of deformation of the hydrogen electrode during firing were evaluated when different types of inorganic fillers were used.

[0055] [Preparation of composition for forming hydrogen electrode] First, nickel oxide (NiO, average particle size: 0.5 μm) and 8% yttria-stabilized zirconia (8% YSZ, average particle size: 0.5 μm) powder were mixed in a mass ratio of 60:40. Then, when the mixed powder was taken as 100 volume %, a commercially available inorganic filler was mixed in such a manner that the volume ratio was shown in the corresponding column in Table 1. As the inorganic filler, alumina mainly composed of a single crystal structure (here, about 70 volume % of the alumina filler as a whole is alumina having a single crystal structure) was used (hereinafter, such an embodiment may be simply referred to as "single crystal"). Then, the obtained mixed powder was kneaded with a pore former (carbon component), a binder (polyvinyl butyral; PVB), a plasticizer, and a dispersion medium (mixed solvent of coal and toluene) in the mass ratio of 58:5:8.5:4.5:24 in this order, to obtain compositions for forming hydrogen electrodes according to Examples 2 to 9. Moreover, except that no inorganic filler was added, a composition for forming a hydrogen electrode according to Example 1 was obtained in the same manner as in Example 2. At this time, the viscosity of the composition for forming a hydrogen electrode according to each example was about 12 Pa s (measured at 25°C, 20 rpm, with a Brookfield Brookfield type viscometer DV3T).

[0056] Here, the inorganic filler according to Example 2 was approximately spherical with an average aspect ratio of 1.0 and an average particle diameter of 0.5 μm. The inorganic fillers according to Examples 3 to 9 had an average major axis of 8.0 μm and an average thickness of about 0.05 μm.

[0057] [Preparation of hydrogen electrode green sheet for evaluation] (Evaluation hydrogen electrode green sheets relating to Examples 1, 2, 4 to 9) First, the hydrogen electrode forming compositions according to Examples 1, 2, and 4 to 7 prepared above were supplied in sheet form onto a carrier film (200 mm length × 350 mm width × 0.2 mm thickness) by blade coating, dried, and then fired at 1400° C. to obtain a plurality of hydrogen electrode green sheets (approximately 0.5 mm thick) according to Examples 1, 2, and 4 to 7. In the blade coating method, the hydrogen electrode forming compositions were discharged at a discharge pressure of 20 kPa from a gap in a blade adjusted to a size of 0.2 mm. Next, the hydrogen electrode green sheets according to Examples 5 and 6 prepared as described above were stacked in the thickness direction (i.e., Y direction) and then stood up so that the stacking surface (i.e., XY plane) was the lower surface. Then, the sheets were cut to a thickness of about 0.5 mm. In this way, the hydrogen electrode green sheets according to Examples 8 and 9 were obtained.

[0058] (Evaluation hydrogen electrode green sheet according to Example 3) A hydrogen electrode green sheet according to Example 3 was produced in the same manner as in Example 1, except that the conditions for the blade coating method were not adjusted as described above.

[0059] [Evaluation of inorganic filler orientation] For the hydrogen electrode green sheets for evaluation according to each example obtained as described above, one or more SEM images (magnification: 2000 times) of a 0.128 mm × 0.096 mm cross section in the thickness direction (corresponding to the XY plane in FIG. 1) were randomly obtained. Such acquisition was performed using JSM-6610 manufactured by JEOL Ltd. Here, in the SEM images according to Examples 4 to 7, it was confirmed that the inorganic filler was generally arranged in a direction perpendicular to the cross section, and in the SEM images according to Examples 8 and 9, it was confirmed that the inorganic filler was generally arranged in the thickness direction of the cross section. Also, in the SEM images according to Examples 2 and 3, it was confirmed that the inorganic filler was randomly arranged (i.e., had no orientation).

[0060] Next, the value of the acute angle θ of the inorganic filler observed in the SEM images of Examples 4 to 7, which is the major axis of the inorganic filler, relative to the direction perpendicular to the cross section, was measured. In addition, the value of the acute angle θ of the inorganic filler observed in the SEM images of Examples 8 and 9, which is the major axis of the inorganic filler, relative to the thickness direction of the cross section, was measured. Note that here, in each example, the measurement was performed on at least 100 inorganic fillers. As a result, it was confirmed that the value of θ was 10° or less for 90% by number or more of the inorganic fillers observed in the SEM images of Examples 4 to 9. The results are shown in the column of "orientation direction of inorganic filler" in Table 1.

[0061] [Durability evaluation of hydrogen electrodes] The hydrogen electrode green sheets for evaluation according to each example prepared as described above were cut into a size of 5 mm length x 50 mm width, and a three-point bending strength test was performed using EZ-test manufactured by Shimadzu Corporation. This test was performed according to the EZ-test manual. If three-point bending with a strength of 70 MPa or more was possible, the durability was evaluated as "◎", if three-point bending with a strength of 50 MPa or more but less than 70 MPa was possible, the durability was evaluated as "○", if three-point bending with a strength of 30 MPa or more but less than 50 MPa was possible, the durability was evaluated as "△", and if three-point bending with a strength of less than 30 MPa was possible, the durability was evaluated as "×". The results are shown in the "Durability of Hydrogen Electrode" column in Table 1.

[0062] [Preparation of SOEC for evaluation] Using the hydrogen electrode-forming compositions according to the respective examples prepared above, SOECs for evaluation were fabricated according to the following procedure. First, the hydrogen electrode forming compositions according to Examples 1 to 7 prepared as described above were repeatedly applied and dried on a carrier sheet (200 mm long x 350 mm wide x 0.2 mm thick) by a doctor blade method under the same conditions as those described in [Preparation of hydrogen electrode green sheets for evaluation] to form a hydrogen electrode support green sheet having a thickness of 0.5 to 1.0 mm. Next, the hydrogen electrode support green sheets according to Examples 5 and 6 prepared as described above were stacked in the thickness direction (i.e., Y direction) and then stood up so that the stacking surface (i.e., XY surface) was the lower surface. Then, the sheets were cut to a thickness of about 0.5 mm. In this way, hydrogen electrode support green sheets according to Examples 8 and 9 were obtained.

[0063] Next, the same nickel oxide powder as above was mixed with 8% YSZ powder in a mass ratio of 55:45. This mixed powder was kneaded with a binder (ethyl cellulose; EC) and a dispersion medium (a solvent mainly composed of terpineol) in a mass ratio of 60:5:35, in that order, and the resulting composition was screen-printed on a green sheet to form a hydrogen electrode active layer. In this way, a hydrogen electrode green sheet according to each example was obtained.

[0064] Next, the same 8% YSZ powder as above, a binder (ethyl cellulose; EC), and a dispersion medium (terpineol; TE) were kneaded in a mass ratio of 65:4:31 to obtain a composition for forming a solid electrolyte. This composition for forming a solid electrolyte layer was then applied onto the hydrogen electrode green sheet by screen printing and dried to form a solid electrolyte layer green sheet with a thickness of about 10 μm.

[0065] In addition, a paste-like composition for forming the reaction suppression layer was prepared by kneading 10% gadolinium-doped ceria powder (10% GDC, average particle size 0.5 μm) as a reaction suppression material, a binder (EC), and a dispersion medium (TE) in a mass ratio of 65:4:31. This was supplied in sheet form onto the solid electrolyte layer green sheet by screen printing and dried to form a reaction suppression layer green sheet with a thickness of approximately 5 μm.

[0066] The laminated green sheet prepared in this way was cut into a circle and co-fired at 1350℃ to obtain a half-cell of SOEC in which the hydrogen electrode support, hydrogen electrode active layer, solid electrolyte layer, and reaction suppression layer were laminated together in this order. After firing, the shape of the half-cell was a circle with a diameter of 20 mm.

[0067] Next, La as an air electrode material 0.6 Sr 0.4 Co 0.2 Fe 0.8 O 3 A paste-like composition for forming an air electrode was prepared by kneading (LSCF, average particle size: 0.5 μm), a binder (EC), and a dispersion medium (TE) in a mass ratio of 80:3:17. This composition for forming an air electrode was then supplied in the form of a circular sheet by screen printing onto the reaction suppression layer of the half cell of the SOEC prepared above, and dried to form an air electrode green sheet. The air electrode green sheet was then fired together with the half cell at 1100° C. to bake it into the half cell, thereby obtaining the SOECs for evaluation in Examples 1 to 9. The dimensions of the air electrode in the obtained SOECs for evaluation were a diameter of 10 mm and a thickness of about 30 μm.

[0068] [Evaluation of hydrogen electrode deformation] The hydrogen electrodes in the evaluation SOECs of each example prepared as described above were evaluated for the presence or absence of deformation. Specifically, the magnitude of warpage of the hydrogen electrodes before and after sintering was evaluated. If the warpage was 0.5 mm or less, the hydrogen electrode deformation was rated as "◎", if the warpage was more than 0.5 mm and less than 1.0 mm, the hydrogen electrode deformation was rated as "○", if the warpage was more than 1.0 mm and less than 1.5 mm, the hydrogen electrode deformation was rated as "△", and if the warpage was more than 1.5 mm, the hydrogen electrode deformation was rated as "×". The results are shown in the "Hydrogen electrode deformation" column in Table 1.

[0069] [Table 1]

[0070] <Second test example> In this test example, the durability of the hydrogen electrode and the degree of deformation of the hydrogen electrode during firing were evaluated when inorganic fillers with different crystallinity were used.

[0071] [Preparation of composition for forming hydrogen electrode] First, a composition for forming a hydrogen electrode according to Example 10 was obtained in the same manner as Example 5, except that alumina mainly composed of a polycrystalline structure (here, about 70 volume % of the entire alumina filler is a polycrystalline structure) was used as the inorganic filler (hereinafter, such an embodiment may be simply referred to as "polycrystalline"). Also, a composition for forming a hydrogen electrode according to Example 11 was obtained in the same manner as Example 6, except that a polycrystalline material was used as the inorganic filler. In Examples 10 and 11, commercially available polycrystalline alumina was used. The average aspect ratio was 0.2, the average minor axis was 1.6 μm, the average major axis was 8.0 μm, and the average thickness was about 0.05 μm.

[0072] [Preparation of hydrogen electrode green sheet for evaluation] Using the hydrogen electrode-forming compositions of Examples 10 and 11 prepared as described above, hydrogen electrode green sheets for evaluation were produced in the same manner as in Example 5 of the first test example.

[0073] [Evaluation of inorganic filler orientation] The orientation of the inorganic filler was evaluated for the hydrogen electrode green sheets for evaluation according to Examples 10 and 11 prepared as described above by the same method as in the first test example. As a result, it was confirmed that the acute angle θ of the inorganic filler with respect to the direction perpendicular to the cross section in the thickness direction in the SEM images of Examples 10 and 11 was 10° or less. The results are shown in the column of "Orientation direction of inorganic filler" in Table 2.

[0074] [Preparation of SOEC for evaluation] Using the hydrogen electrode-forming compositions of Examples 10 and 11 prepared as described above, SOECs for evaluation of each Example were fabricated in the same manner as in the first test example.

[0075] [Evaluation of hydrogen electrode deformation] The hydrogen electrodes of the evaluation SOECs according to the examples prepared as described above were evaluated for the presence or absence of deformation in the same manner as in Test Example 1. The results are shown in the column "Deformation of hydrogen electrode" in Table 2.

[0076] [Table 2]

[0077] As shown in Table 1, it was confirmed that the hydrogen electrodes (cathodes) according to Examples 3 to 9, which contain inorganic fillers with an average aspect ratio of 0.01 to 0.5, were less susceptible to deformation during firing and had improved durability (i.e., mechanical strength) compared to the hydrogen electrodes according to Example 1, which did not contain inorganic fillers, and Example 2, which had an average aspect ratio outside the above range. It was also confirmed that the hydrogen electrodes according to Examples 4 to 9, in which the inorganic fillers had orientation, were more suitably able to suppress deformation during firing and / or improve durability compared to the hydrogen electrode according to Example 3, in which the inorganic fillers did not have orientation. In particular, such effects were remarkably confirmed for the hydrogen electrodes according to Examples 8 and 9. Furthermore, as shown in Table 2, it was confirmed that the durability of the hydrogen electrode and the deformation during firing of the hydrogen electrode were obtained in all of Examples 5 and 6 in which a single crystal inorganic filler was used, and Examples 10 and 11 in which a polycrystalline inorganic filler was used. It was also confirmed that the hydrogen electrodes in Examples 5 and 6 in which a single crystal inorganic filler was used were more suitably suppressed in deformation during firing and had more suitably improved durability than the hydrogen electrodes in Examples 10 and 11 in which a polycrystalline inorganic filler was used.

[0078] As described above, the technology disclosed herein can provide a cathode with improved mechanical strength. It can also provide a hydrogen production device including an electrochemical cell having such a cathode, and hydrogen production using the hydrogen production device. [Explanation of symbols]

[0079] 1. Solid oxide electrolysis cell (SOEC) 10, 10a, 10b Hydrogen electrode (cathode) 12 Solid electrolyte layer 14, 14a, 14b Air pole (anode) 20, 20a, 20b Inorganic filler 30 power supply 40 Main body 41 Introduction 42 Hydrogen electrode side flow channel 43 Collection port 44 Air electrode side flow path 45 Outlet 100 Hydrogen production equipment

Claims

1. 1. A cathode for use in an electrochemical cell, comprising: The cathode includes a matrix made of an inorganic material that functions as a cathode, and an inorganic filler contained in the matrix; the inorganic material includes zirconia having nickel oxide and one or more stabilizers selected from the group consisting of Y2O3, Sc2O3, Yb2O3, Gd2O3, CaO, MgO, and CeO2 dissolved therein; The inorganic filler contains at least one or more of alumina, silica, titanium oxide, and zirconia, the inorganic filler has an average aspect ratio (minor axis / major axis ratio) of 0.01 to 0.5; The cathode is plate-shaped, and when observed in an SEM image of a cross section in a thickness direction of the cathode, for 90% or more of the inorganic fillers by number, the acute angle θ of the major axis of the inorganic filler in either the thickness direction or a direction perpendicular to the cross section is within 10°.

2. 2. The cathode according to claim 1, wherein the inorganic filler has an average minor axis value of 0.05 μm or more and an average major axis value of 10 μm or less.

3. The cathode according to claim 1 , wherein the inorganic filler has a single crystal structure.

4. An electrochemical cell comprising the cathode according to any one of claims 1 to 3, an anode, and a solid electrolyte layer disposed between the cathode and the anode.

5. A hydrogen production device comprising the electrochemical cell according to claim 4.

6. A method for producing hydrogen, comprising producing hydrogen using the hydrogen production device according to claim 5.

Citation Information

Patent Citations

  • High-performance solid oxide electrolytic tank and preparation method thereof

    CN112779555A

  • Layered ceramic capacitor

    JP1992267318A

  • Electrically conductive bonding agent

    JP1998144329A

  • Electrochemical cell

    JP2011210420A

Cited By

  • Composite electrodes with carrageenan for fuel cells

    WO2025250325A1